Studi Multikasus: Epidemi Perilaku Merorok di Kalangan Remaja dan Implikasinya dalam Pendidikan - Mohammad Efendi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
This study describes quantitatively smoking behavior among adolescents through a multi-case study. Based on the information analyzed, it can be concluded that the prevalence of smoking behavior among adolescents is at an alarming threshold, because in terms of quantity the frequency range ranges from 15-50%. Determinants of the development of smoking behavior, especially due to the influence or pressure from the environment and learning through mass media. For this reason, it is advisable to education authorities to minimize the frequency of growth and development of smoking behavior among children and adolescents.